PENGARUH MODEL PEMBELAJARAN CHILDREN LEARNING IN SCIENCE (CLIS) TERHADAP PEMAHAMAN KONSEP MATA PELAJARAN IPA - Idha Magfiroh, Farkhatun; Setiyawati, Enik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to determine whether or not there is an influence of the application of the Children Learning In Science (CLIS) model on the understanding of concepts in science subjects in class IV SDN Gading 160. This type of research is an experiment (pre-experimental design) using a one-group pretest design – posttest design. The sample for this research was class IV students, totaling 29 students. This research obtained the results of hypothesis testing for pretest and posttest data using the Paired Sample T-Test which showed the sig value. 0,000, which means it is smaller than α 0,05 (0,000 < 0,05) so that the hypothesis H0 is rejected and Ha is accepted. The results of the pretest and posttest N-Gain Test showed that the average result obtained was 0.58, which showed a large influence of 58% (medium category). So, there is a significant influence of the application of the children learning in science (CLIS) model on the understanding of science subject concepts for class IV students at SDN Gading 160. Keywords: children learning in science, understanding the concepts of science subjects